Perilaku makan dengan kejadian stunting pada balita: Studi cross-sectional di Kecamatan Nabire Papua - Eka Cahyaningsih Wulandari; Ani Margawati; Ahmad Syauqy; Bagoes Widjanarko; Mohammad Zen Rahfiludin (Poltekkes Kemenkes Aceh, 2024)
Background: Nabire is an area that has more stunting nutrition problems with a percentage of 17.1%. Feeding style by parents need to be considered because it will affect behavior and nutritional intake that support the growth and development of toddlers will provide opportunities for stunting.Objectives: The study aimed to measure the relationship of eating behavior based on parental feeding style with the incidence of stunting in toddlers aged 12 to 59 months in Nabire District, Papua.Methods: This study was conducted observational with cross-sectional design. Subjects were collected using purposive sampling method. Research has been conducted at Karang Tumaritis, Bumiwonorejo, Nabire Kota, and Siriwini Health Centers, in October-December 2023. The sample was 106 toddlers, ages 12-59 months who were taken by non-probability sampling. Data collection on eating behavior based on Parental Feeding Style Questionnaire (PSFQ) and toddler height or body length data measured through anthropometric measurement. Data were analyzed using Chi-square method CI 95%.Results: The results of the study found 46,2% of toddlers were stunted and most respondents (56,6%) had inappropriate eating behavior. The relationship test showed a significant relationship between the incidence of stunting and eating behavior based on parental feeding style (p=0,008 and OR 3,200;95%CI=1,422 – 7,201).Conclution: Eating behavior based on parental feeding style has a significant relationship with the incidence of stunting in toddlers.